Influence of thick-walled cylinders length on the residual stresses generated during the single-cycle mandrelling; IOP Conference Series: Materials Science and Engineering; Vol. 91: VI International Scientific Practical Conference on Innovative Technologies and Economics in Engineering, Yurga, Russia, 21-23 May 2015 - Skvortsov V. F. Vladimir Fedorovich; Boznak A. O. Aleksey Olegovich; Kim A. B. Aleksey Bogovich; Arlyapov A. Yu. Aleksey Yurievich (Innovative technologies for producing and machining materials in mechanical engineering, 2015)
Title screen